Assistance in the Preparation of Tambo Ulayat Books in Nagari Koto Tangah Agam Regency - Syofiarti; Kurnia Warman; Ferdi; Zefrizal Nurdin; Titin Fatimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
The preparation of the land registry book is one of the land management instruments mandated by Regulation of the Province of West Sumatra Number 7 of 2023. This service activity aims to enhance the capacity of the Nagari Government and KAN in preparing the land registry book in Nagari Koto Tangah. The method used is Participatory Action Research, with stages including a data-based land inventory and need identification, stakeholder interviews, socialization, technical training, and evaluation through Focus Group Discussions and interviews. The success of the activity is evaluated based on participant participation levels, increased understanding of the Tambo Ulayat preparation mechanism, the ability to identify land management problems, and the achievement of consensus on the follow-up preparation of the land registry book through participatory methods. The results of the activity show that participants can identify the main issues, including unclear boundaries of customary land, the need for more systematic documentation of physical and legal data, and the importance of involving customary community leaders in the data collection process. This activity also produced technical guidelines for compiling the Customary Land Register. It established a joint commitment between the Local Government and the customary authority (KAN) to continue compiling the Customary Land Register as an initial step in administering customary land. These findings indicate that the PAR approach can support the strengthening of customary institutional capacity and local government administration in the participatory management of customary land. However, the long-term effectiveness of implementation still requires further evaluation.